The radial crack establishing in microcutting of ceramics v3 - Tanović, Ljubomir; Ryzhov, Edward; Karpus, Aleksandr (Journal of Production Engineering, 1994)
Processes developed in the cutting zone while machining ceramics are not entirely explained yet, so hypotheses about forming chips phases differ so much from each other that they are even opposing. In order to have a full survey of phenomena which appear at the diamond grain-ceramics contact, the process of microcutting is realized by a separated diamond grain, and it is established that radial cracks have a great influence in forming chips. In this paper, the results in the field of microcutting of oxide-carbide ceramics type V3 are presented, from the aspect of the point angle of a diamond grain, speed and depth of penetrating which influence the appearance of the angle of radial cracks development.